Gamification in Education: Implementing the Donuts Catcher Game Using Scratch - Afriani, Rinah; Suwari, Ana (Gameology and Multimedia Expert, 2024)
The advancement of technology and gamification in education increasingly showcases the potential to create interactive and enjoyable learning experiences. This study develops the Donuts Catcher game using Scratch, a visual programming platform designed to simplify the creation of games and animations. The game is designed as an educational tool to teach basic programming concepts while providing entertainment for players. In this game, players use a bowl to catch falling donuts, with each successfully caught donut adding points to the player's score. The game ends when the player reaches a maximum score of 100 points. The development process involves designing sprites, backgrounds, and coding interactive and educational game logic. Testing the game demonstrates that Donuts Catcher can be an effective tool for introducing programming to beginners in a fun and easily understandable way. The game also provides engaging gameplay for children, with a simple design that motivates them to keep playing and learning.